Azido- and amido-substituted gallium hydrides supported by N-heterocyclic carbenes. Issue 5 (11th January 2017) - Swarnakar, Anindya K.; Ferguson, Michael J.; McDonald, Robert; Rivard, Eric
Abstract : The synthesis of azido- and amido-gallanes supported by hindered N-heterocyclic carbene donors is reported. Abstract : Despite recent advances in main group N-heterocyclic carbene (NHC) coordination chemistry, gallium hydrides remain, in large part, an unexplored area of research. In this paper we outline efficient routes to azide- and amido-functionalized gallium hydrides such as NHC·GaH2 N3 and NHC·GaH2 N(SiMe3 )2 and explore these species as potential precursors to HGaNH complexes and bulk gallium nitride (GaN).